Built environment and physical activity for the elderly: a systematic review of South Ame - De Paiva, Hermes Koller (2018)
A systematic review was conducted to evaluate studies on the association between the characteristics of a built environment and levels of physical activity (LPA) of elderly people in South America. The searches were conducted on the Bireme, SciElo, Web Of Science and Scopus databases in 2017. Empirical quantitative studies published in Portuguese, English and Spanish, starting in 1990, were included to provide information on the relationship between a built environment and physical activity (PA) for older adults in South America. After the exclusion of repeated titles, 9,592 studies were found, only nine of which were selected, all with a cross-sectional design and samples composed of both sexes, and 77.8% carried out in Brazil. Most of the studies (66.7%) used the abbreviated version of the Neighborhood Environment Walkability Scale (NEWS-A Brazil) to evaluate the built environment and 88.9% used the International Physical Activity Questionnaire to evaluate LPA. Total walking distance (leisure and active transport) was investigated in 22.2% of the studies, leisure PA in 55.5% and displacement PA in 44.4%. The presence of PA facilities and services was associated with LPA, as well as connectivity, street incline and perceived safety. It was concluded that the installation of PA facilities, as well as improved safety, can increase the LPA of the elderly. In addition, satellite image information and audits should be considered when evaluating the built environment.